Management of Village Funds in Implementing Infrastructure Development in Tropodo Village, Krian Distric, Sidoarjo Regency - Fransisca, Risa Salsabilla; Choiriyah, Ilmi Usrotin (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2025)
The purpose of this research is to find out how the Management of Village Funds in the Implementation of Infrastructure Development in Tropodo Knan Village This research uses descriptive qualitative method with data sources obtained and interview data, observation, and documentation. The technique used in determining informants, in this study is purposive sampling technique. The results of this study indicate that the management of village funds in infrastructure development in Tropodo Village starting from the development planning stage has been carried out in accordance with procedures and the community participates in participating in the Musrenbangdes At the development implementation stage, it has been well realized, except for the construction of the Paud building, At the administration stage it has been done well by using the Siskeudes application, but there is still a delay when the treasurer submits the report to the secretary At the reporting stage. Tropodo Village has conducted semi-annual reports to the Regent through the sub-district At the accountability stage, it has been carried out at the end of each fiscal year by submitting a realization report to the Regent through the sub-district and to the village community. Tujuan dan penelitian ini adalah untuk mengetahui bagaimana Pengelolaan Dana Desa dalam Pelaksanaan Pembangunan Infrastruktur di Desa Tropodo Krian Penelitian ini menggunakan metode, kualitatif deskriptif dengan sumber data yang diperoleh dan data wawancara, observasi, dan dokumentasi. Teknik yang digunakan dalam menentukan informan dalam penelitian ini yaitu teknik purposive sampling. Hasil penelitian ini menunjukkan bahwa pengelolaan dana desa dalam pembangunan infrastruktur di Desa Tropodo mulai dari tahap perencanaan pembangunan sudah dilakukan sesuai dengan prosedur dan masyarakat ikut berpartisipasi dalam mengikuti Musrenbangdes Pada tahap pelaksanaan pembangunan sudah terealisasi dengan baik, kecuali pada saat pembangunan gedung Paud, Pada tahap penatausahaan sudah dilakukan dengan baik dengan menggunakan aplikası Siskeudes, namun masih terdapat keterlambatan pada saat bendahara menyerahkan laporan kepada sekretaris Pada tahap pelaporan, Desa Tropodo telah melakukan laporan semesteran kepada Bupati melalui kecamatan Pada tahap pertanggungjawaban, telah dilakukan setiap akhir tahun anggaran dengan menyampaikan laporan realisasi kepada bupati melalui kecamatan serta kepada masyarakat desa.